The edge [compact disc, unabridged] - Baldacci, David (Baldacci, David. 6:20 man thriller., 2023)
When CIA operative Jenny Silkwell is murdered in rural Maine, her laptop and phone were full of state secrets that, in the wrong hands, endanger operatives. Ex-Army Ranger Travis Devine, the 6:20 Man, will have to penetrate the locals' secrets.